Analysis Of Unsafe Acts, Unsafe Conditions, And Near Misses Among Workers At Pertamina Upstream Production Unit In East Kalimantan Region - Eko Marwoto; Yohanes Feryy Cahaya; Herni Pujiati (Management Research Studies Journal, 2025)
This research aims to analyze the factors influencing occupational health and safety (OHS) in Pertamina's upstream production units in East Kalimantan, against the backdrop of increasing attention to safety aspects in the oil and gas sector, which often faces high risks related to unsafe acts, unsafe conditions, and near misses. The main issues identified are low worker compliance with OHS protocols and a lack of awareness and participation in safety training. The methodology used is a descriptive qualitative approach through in-depth interviews, observations, and document analysis. The results indicate that compliance with OHS regulations needs to be improved, particularly in the provision of equipment and personal protective equipment (PPE), as well as enhancing training and outreach programs. The frequency of accident prevention evaluations should be increased, and employee participation in decision-making and OHS incident reporting remains low. It is recommended to conduct regular audits, strengthen OHS communication, schedule interactive training, increase evaluation frequency with published results, and enhance discussion forums and transparent reporting systems with incentives to encourage participation.